1976
DOI: 10.1073/pnas.73.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje cell degeneration, a new neurological mutation in the mouse.

Abstract: A new autosomal recessive mouse mutation, Purkinje cell degeneration (ped), is described. Mutants exhibit a moderate ataxia beginning at 3 to 4 weeks of age. The ataxia results from postnatal degeneration of virtually all cerebellar Purkinje cells beginning around 15 to 18 days of age and progressing rapidly over the next 2 weeks. In addition to the cerebellar disease there is slow progressive degeneration in the retina (photoreceptor cells) and olfactory bulb. Also, adult males have abnormal sperm.Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
415
1
16

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(485 citation statements)
references
References 11 publications
13
415
1
16
Order By: Relevance
“…Newborn (P0) mice of three litters issued of the mating of heterozygous pcd mutant mice (10,11) were also used in this study. Three independent pcd mutations arose spontaneously, but, although the gene Nna1 has been identified as the mutated pcd gene (13), only two pcd strains can be identified by PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborn (P0) mice of three litters issued of the mating of heterozygous pcd mutant mice (10,11) were also used in this study. Three independent pcd mutations arose spontaneously, but, although the gene Nna1 has been identified as the mutated pcd gene (13), only two pcd strains can be identified by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Using both agonists and antagonists of GR and PR, PR mutant mice (PR-KO) and brain specific GR mutant mice (9), as well as potent antioxidant agents we show that the neuroprotective activity of RU486 is independent of its antagonistic properties at PR or GR, and that it is not related to an antioxidant activity. A model of neurodegenerative cell death, i.e., Purkinje cell degeneration (pcd), an autosomal recessive mutation in the mouse, causing the death of all cerebellar Purkinje cells between the second and fourth postnatal weeks (10,11), was also used in this study. We demonstrate that the steroid RU486 highly promotes survival of Purkinje cells in organotypic cultures of cerebellar slices from newborn (P0) pcd mutants mice.…”
Section: Mifepristone (Ru486) Protects Purkinje Cells From Cell Deathmentioning
confidence: 99%
“…Many studies have therefore focused on different ways to decrease PC loss in FAS (7,8). However, different models of ataxia that result from PC death per se (pcd mice, SV4 mice, T147 transgenic mice) have demonstrated that considerable neuropathology can occur without the manifestation of a neurological phenotype and that ataxia occurs in mice only after there is loss of 50-75% of the PCs (9)(10)(11). Because FAS models are characterized by a nonprogressive loss of only 20% of PCs, the presence of an associated neuronal dysfunction can contribute to the observed ataxic phenotype.…”
mentioning
confidence: 99%
“…Similar to other cytosolic carboxypeptidases, the mouse Nna1 protein is broadly expressed in the brain, pituitary, eye, testis and other tissues (Kalinina et al, 2007). Mutations or abnormal expression of Nna1 have been found to cause a pcd phenotype in mice characterized by degeneration of Purkinje cells, mitral cells of the olfactory bulb, thalamic neurons and retinal photoreceptor cells as well as degeneration of sperm (Fernandez-Gonzalez et al, 2002, Mullen et al, 1976. A total of 12 alleles in mouse mutants related to Agtpbp1 have been summarized by the Jackson Laboratory (http:// www.informatics.jax.org/searches/allele_report.cgi?_Marker_key=79447).…”
Section: Discussionmentioning
confidence: 99%